NEW PRODUTS FROM THE DECOMPOSITION OF 2-HYDROXY-1,4BENZOXAZIN-3-ONE (HBOA) A NATURAL LACTAM FROM CE- REALS AND THE 7-NITRODERIVATIVE (HNBOA) - BRAVO,HECTOR R. (Sociedad Chilena de Química, 2000)
The products 3-hydroxy-1,4-benzoxazin-2-one (5) and 5-nitro-2-aminophenolwere isolated from the decomposition reaction of the title compounds inaqueous solutions. Two mechanisms are proposed for the formation of theseproducts.